2017
DOI: 10.1002/ecs2.1757
|View full text |Cite
|
Sign up to set email alerts
|

An irreversible division of labor through a sexually dependent system in the clonal plant Iris laevigata (Iridaceae)

Abstract: Abstract. Scientists were concerned with the division of labor research early, and much current research in clonal plant ecology has proved environmentally induced or a developmentally programmed division of labor. However, the sexually dependent division of labor in clonal plants has received little attention, and few experimental tests have been conducted to date. Here, using reproductive ramets and non-reproductive ramets in the clonal plant Iris laevigata, we test this hypothesis on morphology and physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Compared with vegetative propagation, sexual reproduction is considered to consume more resources and thus to be more nutrient demanding [ 38 ]. For example, the mean biomass of reproductive ramets was nearly twice that of vegetative ramets in Iris laevigata [ 39 ]. However, we found that the mean biomass of reproductive ramets was 27.2% that of vegetative ramets in H. glabra ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with vegetative propagation, sexual reproduction is considered to consume more resources and thus to be more nutrient demanding [ 38 ]. For example, the mean biomass of reproductive ramets was nearly twice that of vegetative ramets in Iris laevigata [ 39 ]. However, we found that the mean biomass of reproductive ramets was 27.2% that of vegetative ramets in H. glabra ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The annual precipitation in this region averages 704.2 mm and the mean temperatures in January and July are–15.7 and 22.5 °C, respectively. The vegetation type is classified as Changbai Mountain flora; the original vegetation, which mainly comprised Pinus koraiensis and broad-leaved mixed forests, has degraded into a secondary broad-leaved forest ( Wang et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The translocation of resources to emerging ramets and the significant role of physiological integration in the early development of new ramets (e.g., Hartnett and Bazzaz, 1983;Alpert, 1996;Xu et al, 2012), as well as marked changes in patterns of resource translocation from maternal ramets to daughter ramets across ramet ontogeny, are well documented in the literature (Duchoslavová and Jansa, 2018), but studies on the translocation of resources between vegetative ramets and reproductive ramets are lacking. Although only one study found that vegetative ramets could transfer their nutrients to adjacent reproductive ramets through the rhizome at the flowering stage in an ornamental clonal plant Iris laevigata (Wang et al, 2017b), the research focused on a single point in reproductive development. It is unclear how translocation of nutrients changes with the process of reproductive development.…”
Section: Nutrient Translocation During Reproductive Developmentmentioning
confidence: 99%
“…In fact, clonal fragments often contain ramets that are at different developmental stages or belong to different types, such as parental ramets and daughter ramets or vegetative ramets and reproductive ramets. For example, some studies found that the benefits of physiological integration in a homogeneous environment existed both between ramets of different ages with developmental differences (Stuefer, 1998;Yu et al, 2002;Dong et al, 2015;Zhang et al, 2016) and between ramets of different types with production differences (Wang et al, 2017b). Therefore, even under the same levels of external resource supply, resource sharing between interconnected ramets might improve clonal performance owing to differences in the amounts of absorbed or assimilated resources.…”
Section: Introductionmentioning
confidence: 99%